2014
DOI: 10.1371/journal.pone.0092376
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy as a Factor Protective against Anal Dysplasia in HIV-Infected Males Who Have Sex with Males

Abstract: ObjectivesChronic infection with oncogenic HPV genotype is associated with the development of anal dysplasia. Antiretroviral therapy (ART) has been shown to decrease the incidence of cervical carcinoma in women with HIV. We sought to: 1) describe the prevalence and grade of anal dysplasia and HPV infection in our study subjects; 2) analyze the grade of correlation between anal cytology, PCR of high-risk HPV, and histology; 3) identify the factors associated with the appearance of ≥AIN2 lesions.DesignCross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 30 publications
(40 reference statements)
2
21
0
4
Order By: Relevance
“…We know that condylomata acuminata are usually caused by HPV 6 and 11 and therefore show no progression to AC. Yet some studies have identified anogenital condylomata acuminata as a single risk factor for the development of high grade AIN . These findings stress the importance of HRA where AIN and condylomata acuminata can clinically be distinguished by the experienced examiner and in case of unclear clinical presentation a biopsy should be taken.…”
Section: Discussionmentioning
confidence: 95%
“…We know that condylomata acuminata are usually caused by HPV 6 and 11 and therefore show no progression to AC. Yet some studies have identified anogenital condylomata acuminata as a single risk factor for the development of high grade AIN . These findings stress the importance of HRA where AIN and condylomata acuminata can clinically be distinguished by the experienced examiner and in case of unclear clinical presentation a biopsy should be taken.…”
Section: Discussionmentioning
confidence: 95%
“…Many epidemiological studies have been conducted to investigate anal HPV prevalence among HIV-infected MSM in several countries and regions. Anal HPV prevalence in HPV-infected MSM was 61.0% of 92 patients in the United States [3], 74.2% of 140 in Spain [4], 75.9% of 361 in Japan [5], 82.7% of 133 in Korea [6], 88.6% of 166 in Italy [7], 91.8% of 85 in South Africa [8], and 95.5% of 1439 in Spain [9]. The high prevalence of anal HPV infection observed in the present study is similar to that previously reported in other countries.…”
Section: Discussionmentioning
confidence: 95%
“…The most common atypia was LSIL (22.6%), followed by ASCUS (19.5%), and HSIL (0.8%). An epidemiological study conducted in Spain among HPV-infected MSM revealed a high HR-HPV prevalence (74.2%), and 54.2% of cytological atypia, such as LSIL (49.2%), ASCUS (2.5%), and HSIL (2.5%) [4]. Wilkin et al also found that 47% of 85 HIV-infected men had abnormal results: LSIL (24%), ASCUS (18%), and HSIL (6%) [3].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, cART and associated immune reconstitution decrease the risk of pre-malignant cervical and anal HPV-associated HSIL among HIV-infected individuals 148 . Indeed, well-controlled HIV viremia is associated with half of the risk of developing cervical or anal HSIL after adjusting for CD4 + T-cell counts 149 .…”
Section: Cancer Prevention Interventionsmentioning
confidence: 99%